FDIs and investment policy in some European countries after their EU accession. Challenges during the crisis - Magdalena RADULESCU; Elena Nolica DRUICA (Revista Romana de Economie, 2011)
The aim of this paper is to find out to what extent the accession countries will be able to benefit from an increase in the quality of foreign direct investments (FDIs) that they receive due to EU membership. Although there will be some investment in new affiliates resulting in greenfield subsidiaries, transnational companies (TNCs) may divest their operations in response to better location advantages elsewhere in the EU (as Spain and Portugal are experiencing because their low-cost advantages are eroded). In many Central and Eastern European (CEE) countries, the share of foreign ownership in total capital stock is already typically much higher than in older EU member states, but we can already observe a trend of relocating TNCs’ subsidiaries to other emerging countries in order to diminish the costs, in the context of the present crisis and we believe that this trend will continue in the future, especially in the crisis context when the inceptive burden is heavy for governments. The conclusion of this paper is that the CEE countries haven’t faced quite similar conditions as the Southern European countries that acceded to the EU in the ‘80s. So, their benefits have considerably diminished and the present crisis didn’t help them at all to reduce their economic gaps comparing to the developed European countries.